Sounding a Crip Aesthetic: Transforming the Sonic in Samuel Beckett’s Not I - Johnson, Megan (Performance Matters, 2020)
This article analyzes a recent production of Samuel Beckett’s play Not I performed by Jess Thom, a neurodiverse performer most well known by the moniker Touretteshero. Not I is a monologue of twisting and fragmented text revered for the physical, vocal, and emotional challenge it presents to performers and audiences alike. This article takes up the aesthetic, material, and sonic changes made to the play in the Touretteshero production, which serve to reimagine and reconstruct the “sonic profile” of the work. Together, these changes enact a crip aesthetic that illuminates the often-hidden exclusionary structures that permeate theatrical practice. Specifically, this article describes the material changes made to the production in the service of increased accessibility for performer and audience, how Thom’s vocal tics interact with Beckett’s already fragmented text, and how the production’s integration of sign language interpretation extends how we conceptualize sound. Through this analysis, Thom’s performance emerges as a revolutionary contribution to contemporary disability arts that reimagines the value of disability and the possibilities for sound in performance.